Innovative Approach For Production Of Epoxy Syntactic Foams Consisting Of Epoxy Hollow - Mutalib, Nor Azaniza Abdul (2015)
Epoxy spheres were fabricated via coating technique which utilized series of epoxy/curing agent mixture onto expanded polystyrene beads (EPS) formulated at ratio of 1:0.5 (epoxy rich), 1: 1(equivalent ratio) and 1:2 (amine rich) and their characteristic were investigated in term of differential scanning calorimeter (DSC), appearance and compressive behaviour. The results showed that EHS produced using epoxy/curing agent ratio of 1:1, exhibited smooth coating surface and yielded strong shell structure reflected from analysis of curing characteristic using DSC technique. An innovative approach involving vacuum assisted technique for preparation of syntactic foam made of epoxy hollow spheres and epoxy resin was introduced to be compared with syntactic foam produced through conventional technique; mold-casting technique. In this study, the resultant specimen was characterized for density and compression properties. Effect of different processing techniques on specimen was analysed through stress-strain curve and failure pattern of the syntactic foam filled EHS with the same EHS size. The vacuum assisted technique has successfully reduced voids within the matrix that was produced due to the processing technique and subsequently resulted in higher compressive strength and modulus. Specimen produced by the vacuum assisted technique was further investigated by varying several aspects in terms of cell sizes (BASF 403, BASF 303 and B-Normal) and internal structure of EHS (supported and unsupported). The effect of compression test orientation on the specimen failure pattern was also examined to assist in explaining in stress-strain curve difference. Under compressive loading, the failure initiated when stress concentrated on the weakest epoxy spheres slowly propagated through adjacent spheres and displayed wider horizontal plateau. When almost all sphere have been successfully collapsed, there was a drastic increase in stress on the stress-strain curve and this indicated that failure mechanism occurred via uniform densification throughout the specimen.